The effect of an android-based application on T-Mobile learning model to improve students' listening competence. (March 2019) - Herry Setyawan, Wawan; Budiman, Agus; Septa Wihara, Dhiyan; Setyarini, Triana; Nurdyansyah,; Rahim, Robbi; Barid Nizarudin Wajdi, Muh
Abstract: This paper proposes is to improve the competence of students' listening by applying T-Mobile learning model that on android-based learning application. An approach to designing and developing the interactive mobile application T-Mobile Learning for learner with special needs, suitable for the Android based mobile operating system, is presented. In the literature, these students are referred to as learner with special educational needs. This study uses a quantitative experimental research with pretest group design and posttest control. It consisted of seventy-two students with random sampling technique. The result of the analysis shows that there is a significant difference between the competence of the students' listening which is taught using T-Mobile Learning application with listening based assisted picture.